Green Energy and Efficiency:An Economic Perspective - Ansuategi, Alberto (Springer, 2015)
Addressing the major issues associated with green energy and energy efficiency, this book examines the economics of energy from the theoretical as well as applied perspectives. It makes a valuable contribution to existing discussion around environment and climate change issues, and provides an analysis of the socioeconomic and policy-oriented aspects of this topic. Each chapter is self-contained and tackles the fundamental issues and latest developments of a particular sub-topic. Combining rigour and accessibility, this book allows non-specialized readers to understand the complexity of the topic, and to likewise access the most relevant and up-to-date literature. It simultaneously enables more specialized readers to broaden their understanding of complex energy topics and it provides a comprehensive overview of the cutting-edge developments of the issues covered by the book.